2016
DOI: 10.1016/j.appet.2016.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Failure of sucrose replacement with the non-nutritive sweetener erythritol to alter GLP-1 or PYY release or test meal size in lean or obese people

Abstract: There is considerable interest in the effect of foods containing high intensity sweeteners on satiation. However, less is known about low-calorie bulk sweeteners such as erythritol. In this randomized three-way crossover study, we studied 10 lean and 10 obese volunteers who consumed three test meals on separate occasions: (a) control sucrose meal; (b) isovolumic meal with partial replacement of sucrose by erythritol; (c) isocaloric meal which contained more erythritol but equivalent calories to the control mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
40
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 30 publications
7
40
0
1
Order By: Relevance
“…A review of each article according to the quality criteria checklist (13) rated the quality of nineteen of the twenty-one studies as positive. A total of two studies were rated neutral as participant selection was not described (19,20) (online Supplementary material I). Based on the NHMRC level of evidence (15) , all except three studies (21)(22)(23) were randomised controlled trials (level II).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A review of each article according to the quality criteria checklist (13) rated the quality of nineteen of the twenty-one studies as positive. A total of two studies were rated neutral as participant selection was not described (19,20) (online Supplementary material I). Based on the NHMRC level of evidence (15) , all except three studies (21)(22)(23) were randomised controlled trials (level II).…”
Section: Resultsmentioning
confidence: 99%
“…Included studies evaluated the effects of AS consumption through food (n 5), beverages (n 12) or a combination of foods and beverages (n 2) over a period of time ranging from 1 d (20,(24)(25)(26)(27)(28)(29)(30)(31)(32) to 6 months (33) . Characteristics of included studies are displayed in Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that most sugar alcohols can prevent tooth decay and act as prebiotics to promote the growth of the beneficial bacteria in the gut (Belloir et al, 2017). They may also promote gut hormone release and have been used as a sugar alternative for people with diabetes (Overduin et al, 2016).…”
Section: Sugar and Sugar Alcoholsmentioning
confidence: 99%
“…A recent study demonstrated that xylitol and erythritol intake can stimulate GLP-1 and CCK release in the gut of both lean and obese subjects (Wölnerhanssen et al, 2016). Overduin et al (2016) reported that erythritol has a similar effect on trigger and control GLP-1 and PYY release in lean (not obese) subjects compared with sucrose. Similar in vitro results indicated that both sugars and artificial sweeteners (e.g.…”
Section: Physiological Effect Of Sweeteners and Sweet Taste Receptorsmentioning
confidence: 99%